IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA DEPOK - Sesario Fernandes; Serly Wulandari (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2020)
One of the functions of government is service. Of function the government presence in providing services to the community is very important included in the Child Identity Card (KIA) services. Depok city government through agency of population and civil registration Depok implemented the program Child Identity Card Depok City since 2015. But, the release of ministerial regulation number 2 year 2016 about Child Identity Card, KIA Depok City have been issued since 2015, should be replaced by KIA national scale. This research using methods descriptive with a qualitative approach. The operationalization of the concept of this research using the theory of the Implementation Of Policy Edwards III as to dimensions among other: communication, resources, disposition, as well as the structure of bureaucracy. Data sources in the form of person, place and paper. Data collection techniques through interviews, observation and review of documentation. Informants this research set in purposive sampling and insidental sampling. Technique data analysis through editing stage, classiϔication and interpretation. The research results show that the implementation of Policy KIA on the agency of Population and Civil registration Depok City is not optimal caused by 4 variable not in the condition of being ideal. Keywords: The Implementation Of Policy, Child Identity Card